Abordagem conservadora em restaurações posteriores com compósitos: acompanhamento clínico de 2 anos (2019)
Replacement of defective restorations with new ones has been a major reason for restorative procedures. However it is known that during the removal of the old material there is a progressive increase of the cavity size, weakening the healthy dental remnant. Modern dentistry and the advent of adhesive protocols allow the dentist to opt for a more conservative treatment plan. As an alternative to the total replacement of the restoration, both the surface re-polishing can be performed, restoring smoothness and gloss or restorative repair, which with the addition of composite can reanatomize and regularize the color of restorations of old, but well-adapted resins. The present article aims to make a clinical case report of a conservative approach in posterior composite restorations, demonstrating the technique and clinical success after a two - year follow - up.